La IA como noticia: temas y encuadres de la inteligencia artificial en medios digitales costarricenses - Tristán Jiménez, Larissa (2026)
This article examines media coverage of artificial intelligence (AI) in nine Costa Rican digital media outlets to identify the main themes and frames associated with AI. We conducted a content analysis on a corpus of 348 news articles published in 2022 and 2024. The results show a sustained increase in media coverage of the phenomenon and a diversification of topics, shifting from a predominantly technological and labor-focused representation to the inclusion of sociocultural and educational dimensions in news stories on the subject. Regarding frames, there is a shift from the explanatory frame –dominant in 2022– to approaches focusing on technological, ethical, and evaluative impacts in 2024. Information on AI relies on international content reinterpreted in a local context, a process conceptualized as a form of discursive tropicalization of AI. The study concludes that, despite the observed diversity, coverage tends to prioritize the presentation of results over explaining the technical processes underlying the functioning of this technology, raising questions from the perspective of epistemic justification. This contributes to the study of AI as a news subject in Latin American contexts.